City bountiful : a century of community gardening in America - Lawson, Laura J., 1966- (University of California Press, 2005)
Since the 1890s, providing places for people to garden has been an inventive strategy to improve American urban conditions. There have been vacant-lot gardens, school gardens, Depression-era relief gardens, victory gardens, and community gardens - each representing a consistent impulse to return to gardening during times of social and economic change. In this critical history of community gardening in America, the most comprehensive review of the greening of urban communities to date, Laura J. Lawson documents the evolution of urban garden programs in the United States. Her vibrant narrative f.